Focal cortical dysplasia type IIb in the rolandic cortex: Functional reorganization after early surgery documented by passive task functional MRI - Barba, Carmen; Montanaro, Domenico; Frijia, Francesca; Giordano, Flavio; Blümcke, Ingmar; Genitori, Lorenzo; De Masi, Francesco; Guerrini, Renzo (Epilepsia, 2012)
Summary Surgery for seizures arising from the rolandic area can be performed effectively, and accurate mapping of eloquent regions may improve seizure and functional outcome. Noninvasive cortical mapping is, however, hardly feasible in young children. We studied two children with epileptogenic focal cortical dysplasia (FCD) type IIb in the rolandic area, in whom preoperative passive task functional MRI (fMRI) during sedation helped planning a tailored surgical approach. In one patient the dysplastic cortex was functionally activated. After complete lesionectomy both children exhibited motor impairment that readily improved. Repeat fMRI, performed after complete (Patient 1) or partial (Patient 2) recovery, demonstrated relocation of motor-related activations posterior to the area of resection. fMRI during sedation can be used to demonstrate postsurgical functional reorganization of the motor cortex in young children. There is interindividual variability in functional activation of FCD type IIb. © 2012 International League Against Epilepsy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Epilepsy surgery; Focal cortical dysplasia; Functional MRI; Sedation